FERTILITY IN WOMEN AFTER LAPAROSCOPIC SALPINGOSTOMY WITH EVACUATION OF THE EMBRYO IN THE TREATMENT OF ECTOPIC TUBAL PREGNANCY - Лариса Егоровна Фетищева; Вадим Гельевич Мозес; Кира Борисовна Мозес (The Publishing House Medicine and Enlightenment, 2019)
The aim of the research - to study fertility in women after laparoscopic salpingostomy with the evacuation of the embryo in the treatment of ectopic pregnancy. Materials and methods. Fertility was studied in 121 women with ectopic tubal pregnancy, who underwent salpingoectomy or salpingostomy. The primary outcome of treatment was the frequency of occurrence of spontaneous uterine pregnancy at 15 months of follow-up after surgery. The secondary outcome of the treatment was the frequency of adhesions in the small pelvis, the frequency of patency of the operated fallopian tube and the frequency of restoration of its patency after plastic surgery, according to the data of chromohydrotubation at 3 months. Results. During second-look laparoscopy in patients of both groups at 3 months of observation, adhesions in the pelvis prevailed (66.2 % and 75.6 %, respectively, p = 0.29), the operated fallopian tube was passable in 24.3 % of women comparison groups, whereas 75.6 % of the operated fallopian tube was impassable. Plastic surgery of the operated fallopian tube was performed in 75.6 % of women, after which 68.2 % of its patency was restored. The frequency of spontaneous uterine pregnancy after organ-sparing surgical treatment of ectopic pregnancy at the 15th month of observation was 14.6 % (2.5 % in control, p = 0.011). Conclusion. When choosing the volume of surgical treatment for ectopic tubal pregnancy, it is reasonable to use a laparoscopic salpingostomy with the evacuation of the embryo. This operation was accompanied by the restoration of the patency of the fallopian tube in some patients and the preservation of fertility. However, laparoscopic salpingostomy with evacuation of the embryo was more often accompanied by repeated reconstructive operations and recurrent ectopic pregnancy in the operated fallopian tube. All this justifies the search for new methods of organ-preserving surgery in ectopic tubal pregnancy.